Research Note: Comparison of the texture, structure, and composition of eggs from local Chinese chickens and a highly selected line of egg-type chickens and analysis of the effects of lipids on texture - Ruiqi Zhang; Jianwen Deng; Xingze Li; Wenxi Shang; Zhonghua Ning (Poultry Science, 2022)
ABSTRACT: Egg yolk texture affects consumer egg preference. The sensory characteristics of eggs are affected by not only the cooking method but also the maternal breed. In this study, we investigated the texture, structure, and nutritional differences between the cooked yolks of eggs obtained from Hetian Dahei (HTDH) and Rhode Island Red (RIR) chickens. The springiness, cohesiveness, gumminess, chewiness, and resilience of HTDH egg yolks were lower, and the hardness was higher than those of RIR egg yolks. Moreover, scanning electron microscopy revealed that HTDH egg yolk particles were smaller and that HTDH egg yolks had a denser protein network than those of RIR egg yolks. Lipid and protein levels were higher, whereas water contents were lower in uncooked HTDH egg yolks than in uncooked RIR egg yolks. Liquid chromatography tandem mass spectrometry further revealed that lower cohesiveness was associated with higher levels and greater variety of lipids in egg yolks. Moreover, increased phospholipid levels reduced egg yolk cohesiveness. Thus, the eggs of local Chinese chicken breeds were superior to those of a highly selected broiler chicken breed in terms of texture, structure, and nutritional composition, which may influence egg variety selection.